Vitamin B12 - Smith, A; Warren, M; Refsum, H (Elsevier, 2018)
The biosynthesis of B 12 , involving up to 30 different enzyme-mediated steps, only occurs in bacteria. Thus, most eukaryotes require an external source of B 12 , and yet the vitamin appears to have only two functions in eukaryotes: as a cofactor for the enzymes methionine synthase and methylmalonylCoA mutase. These two functions are crucial for normal health in humans, and in particular, the formation of methionine is essential for providing methyl groups for over 100 methylation processes. Interference with the methionine synthase reaction not only depletes the body of methyl groups but also leads to the accumulation of homocysteine, a risk factor for many diseases. The syndrome pernicious anemia, characterized by lack of intrinsic factor, leads to a severe, sometimes fatal form of B 12 deficiency. However, there is no sharp cutoff for B 12 deficiency; rather, there is a continuous inverse relationship between serum B 12 and a variety of undesirable outcomes, including neural tube defects, stroke, and dementia. The brain is particularly vulnerable; in children, inadequate B 12 stunts brain and intellectual development. Suboptimal B 12 status (serum B 12 < 300pmol/L) is very common, occurring in 30%-60% of the population, in particular in pregnant women and in less-developed countries. Thus, many tens of millions of people in the world may suffer harm from having a poor B 12 status. Public health steps are urgently needed to correct this inadequacy.